The Relationship between Nurses' Knowledge and Compliance with the Implementation of Patient Safety Goal Standards in accordance with STARKES 2022 - Setiowati, Sulis; Widiatie, Wiwik; Mukaromah, Indah (Promotion and Prevention in Mental Health Journal, 2022)
Patient safety in hospitals is a form of guarantee that care for patients becomes safer. Patient Safety Goal accreditation standards are the main thing that must be done, especially by health workers who work in hospitals, because they are closely related and will affect the quality of service in hospitals. Preliminary studies show that nurses' knowledge and compliance with implementing patient safety target standards still need to be improved. This study aimed to determine nurses' knowledge of implementing compliance with Patient Safety Goal standards according to STARKES 2022. This research design is a correlation analytic with a cross-sectional approach. The population was all nurses at the Jombang Hospital Inpatient Installation, totaling 184 respondents. The sample in this study amounted to 126 respondents, obtained through the probability sampling technique (proportionate stratified random sampling). Measuring instruments in the form of questionnaires and observation sheets. The Spearman Rho test analyzed data with p-value <α (0.05). The results showed a relationship between the level of knowledge and compliance with implementing patient safety target standards with a p-value of 0.000 <0.5, where the correlation level was 0.466. The higher the nurse's knowledge, the higher the nurse's compliance in implementing patient safety target standards.